Bimbingan Orang Tua Terhadap Pasangan yang Menikah di Usia Dini di Desa Keretak Kecamatan Sungai Selan Kabupaten Bangka Tengah Provinsi Kepulauan Bangka Belitung - Musdalifah Musdalifah (Counselle| Journal of Islamic Guidance and Counseling, 2021)
This research is motivated by the promiscuity of teenagers which results in frequent truancy, dropping out of school, getting pregnant out of wedlock. This results in marriage at an early age, even though physically and psychologically they are not ready so that parental guidance is needed for couples who marry at an early age. The purpose of this study was to find out the guidance for married couples who had been married at an early age in the village of Keretak Central Bangka, as well as to find out the factors that influence the guidance for the couple. This research is descriptive qualitative. Data was collected using unstructured interview techniques, observation, and documentation. The data that has been collected is then analyzed using the Miles and Huberman model. The results showed that guidance for couples who married at an early age turned out to be one solution for the development and increase in activities in the family. Likewise, couples who marry at an early age are able to maintain harmonious domestic relations.